Performance measures of ISM-band and conventional telemetry. - Baker, S.D (IEEE Engineering in medicine and biology magazine)
The primary goal of this study is to quantify the communications reliability of telemetry systems using ISM-band two-way communications technology and contrast it to that of VHF/UHF-based systems from an empirical and clinical perspective. The principal criterion variable of communications reliability was total dropout proportion: the percentage of wireless patient monitoring time attributable to a loss of patient signal. Data from 17 institutions across the United States were included in this research. The data from this study were also used to explore potential relationships between communications reliability and various institutional factors. The institutional variables evaluated for possible adverse impact on ISM-band communications reliability included wireless coverage area, the number of telemetry transmitters supported, institutional experience with the product, gross institution size, and the number of telemetry systems within each hospital. The frequency-hopping communication technology utilized by the ISM-band products was not adversely affected by coexisting ISM-band devices. Institutions with shared ISM-band environments demonstrated a better - but statistically insignificant - performance difference both in terms of total dropout proportion and mean time between dropouts. Analysis showed no adverse affect on the communications reliability of ISM-band systems as a function of the number of telemetry transmitters supported, institution size, number of ISM-band telemetry systems within an institution, coverage area, or institutional experience with the system. In contrast, VHF/UHF installations showed statistically significant adverse impact on dropout proportion from two sources: the more transmitters supported, or the greater the coverage area, the higher the dropout proportion. The results from regression analysis at the institution-level should be interpreted cautiously since the statistical power was limited by the number of hospitals in the sample.